Complete Genome Sequence of Serratia Phage Muldoon - Campbell, Soren (Microbiol Resour Announc, 2020)
Serratia marcescens is a ubiquitous Gram-negative bacterium that is linked with emerging opportunistic infections. In this report, we describe the isolation and annotation of an S. marcescens myophage called Muldoon. Related to T4-like phages, such as Serratia phage PS2, Muldoon contains 257 predicted protein-coding genes and 4 tRNA genes.